2014
DOI: 10.1093/jae/eju028
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Border Banking and Financial Deepening: The African Experience

Abstract: Cross-border banking has been important across

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…10, No. 3;2018 These results indicated that the VIF values of the independent variables were within the threshold of 10. This indicated that that there was no threat of multicollinearity problem and therefore, the study used linear regression model.…”
Section: Multicollinearitymentioning
confidence: 70%
See 4 more Smart Citations
“…10, No. 3;2018 These results indicated that the VIF values of the independent variables were within the threshold of 10. This indicated that that there was no threat of multicollinearity problem and therefore, the study used linear regression model.…”
Section: Multicollinearitymentioning
confidence: 70%
“…10, No. 3;2018 Kenyan during the study period. Earlier, a number of studies have been carried out to establish the effect of macroeconomic factors on bank stability and have revealed mixed effects with some proposing a negative effect while others a positive effect.…”
Section: Financial Inclusion Gdp Growth Rate and Credit Riskmentioning
confidence: 96%
See 3 more Smart Citations